 Download Download Presentation CHAPTER 2 RevIEw

# CHAPTER 2 RevIEw

Download Presentation ## CHAPTER 2 RevIEw

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -
##### Presentation Transcript

1. CHAPTER 2 RevIEw precalculus

2. y = (x+2)2

3. y = (x-2)2 -1

4. y = -(x+1)2 + 3

5. 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.

6. 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.

7. 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.

8. 4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth. 59.4 MPH

9. 5) f(x) = x2 - 16

10. 5) f(x) = x2 - 16 = (x )(x )

11. 5) f(x) = x2 - 16 = (x - 4)(x + 4)

12. 5) f(x) = x2 - 16 = (x - 4)(x + 4) zeros: 4, -4

13. 6) f(x) = x2 + 12x + 36

14. 6) f(x) = x2 + 12x + 36 = (x )(x )

15. 6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6)

16. 6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6) zeros: -6, -6

17. 7) f(x) = 2x2 - 14x + 24

18. 7) f(x) = 2x2 - 14x + 24 = 2( )

19. 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12)

20. 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x )(x )

21. 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3)

22. 7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3) zeros: 4, 3

23. 8) f(x) = x4 - x3 - 20x2

24. 8) f(x) = x4 - x3 - 20x2 = x2( )

25. 8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x)

26. 8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x )(x )

27. 8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x + 4)(x - 5)

28. 8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5)

29. 8) f(x) = x4 - x3 - 20x2 = x2(x2- x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5) zeros: 0, 0, -4, 5

30. Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2)

31. Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) • (x + 7)(x - 2)

32. Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) • (x + 7)(x - 2) • x2 - 2x + 7x - 14

33. Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) • (x + 7)(x - 2) • x2 - 2x + 7x - 14 • x2 + 5x - 14

34. 10) 0, 4

35. 10) 0, 4 (x - 0)(x - 4)

36. 10) 0, 4 (x - 0)(x - 4) x(x - 4)

37. 10) 0, 4 (x - 0)(x - 4) x(x - 4) x2- 4x

38. What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right

39. What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right

40. What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right

41. 12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right

42. 12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right

43. 12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right

44. 13) f(x) = 6(x4 + 3x2 + 2)rises to the left rises to the right falls to the left falls to the right

45. 13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right

46. 13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right